Social dentistry program and its relationship with the oral health knowledge in six schools in Lima and Huancayo. - Pariajulca Fernández , Israel Robert (2023)
Objective: To determine the effectiveness of the social dentistry program (POS) and its relationship with the oral health knowledge of teachers, parents and caregivers in six schools in Lima and Huancayo. Material and Methods: The study was prospective, longitudinal and explanatory. Where knowledge of oral health, oral health status, age, sex and educational level were considered. The sample consisted of students between the ages of 11 and 12, teachers and caregivers who attended the six public schools. Validated questionnaires and an epidemiological record were used for data collection. Results: the average knowledge score on oral health before the application of the POS in the group of teachers was 12.3 ± 1.4, and after the application of the POS it was 27.9 ± 1.9. The average oral health knowledge score before the POS in the group of caregivers is 12.5 ± 1.6, and after the POS it was 17.3 ±1.2. The average oral health knowledge score before the application of the POS in the student group was 12.5 ±1.6, and after the POS it was 17.3 ±1.2. Finally, the average IHOS score before the application of the POS in the student group was 2.7 ± 0.5, and after the POS it was 0.3 ± 0.2. Conclusions: the application of the POS increased the knowledge about oral health of teachers, caregivers and students.